EIF2S1 Silencing Impedes Neuroblastoma Development Through GPX4 Inactivation and Ferroptosis Induction - Zhen Li; Yunhui Wang; Shubin Liang; Tingdong Yuan; Jing Liu (International Journal of Genomics)
Conclusion: Our findings indicate that EIF2S1 appears to facilitate the progression of NB by protecting tumor cells from ferroptosis through modulating GPX4 and SLC7A11 expression. Consequently, EIF2S1 may serve as a potential therapeutic target for the management of NB.